Evaluation on the adsorption capabilities of new chemically modified polymeric adsorbents with protoporphyrin IX - Jung, MW; Ahn, KH; Lee, Y; Kim, KP; Paeng, IR; Rhee, JS; Park, JT; Paeng, KJ (ELSEVIER SCIENCE BV, 2001)
A chemically modified polymeric adsorbent was synthesized to evaluate the availability as an adsorbent for solid-phase extraction (SPE) of phenol and chlorophenols. Commercially available Amberlite XAD-2 and XAD-4 resins were modified with macrocyclic protoporphyrin IX (PPIX) through the ketone linkage. Adsorption isotherms were obtained by batch experiments and the data were fitted to the Freundlich equation to calculate the adsorption parameters. Breakthrough volumes were measured by column experiments. Physical properties such as surface area, average pore diameter and micropore volume of resins were measured to correlate with the adsorption characteristics. As a result, adsorption capacity was increased for the chemically modified resins and it can be concluded that the increase of pi-pi interaction due to the introduction of the porphyrin molecule is the major factor for the increase of the adsorption capacity. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: SOLID-PHASE EXTRACTION; LIQUID-CHROMATOGRAPHY; PHENOLIC-COMPOUNDS; STATIONARY PHASES; REVERSED-PHASE; WATER; RESINS; PORPHYRINS; PESTICIDES; SORBENTS